2021
DOI: 10.3389/fnagi.2021.676618
|View full text |Cite
|
Sign up to set email alerts
|

A Graph Theory Approach to Clarifying Aging and Disease Related Changes in Cognitive Networks

Abstract: In accordance with the physiological networks that underlie it, human cognition is characterized by both the segregation and interdependence of a number of cognitive domains. Cognition itself, therefore, can be conceptualized as a network of functions. A network approach to cognition has previously revealed topological differences in cognitive profiles between healthy and disease populations. The present study, therefore, used graph theory to determine variation in cognitive profiles across healthy aging and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 106 publications
1
23
1
Order By: Relevance
“…Studies have demonstrated that the human brain's network has small-world properties, re ecting the optimal balance of e ciency and cost (Farahani et al, 2019). However, the pathological injury may affect network organizations differently, resulting in cognitive impairment (delEtoile & Adeli, 2017; Wright et al, 2021). Some studies have used graph-theoretic analysis to characterize the topological changes of neural networks in cognitive disorderrelated disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that the human brain's network has small-world properties, re ecting the optimal balance of e ciency and cost (Farahani et al, 2019). However, the pathological injury may affect network organizations differently, resulting in cognitive impairment (delEtoile & Adeli, 2017; Wright et al, 2021). Some studies have used graph-theoretic analysis to characterize the topological changes of neural networks in cognitive disorderrelated disorders.…”
Section: Introductionmentioning
confidence: 99%
“…"Cognitive landmarks" then can refer to cognitive functions and/or changes in them over time, such as maturation or decline. Studies in Table 1 sought to investigate both the arrangement of interrelationships amongst variables (e.g., Ferguson for the Alzheimer's Disease Neuroimaging Initiative, 2021; Jonker et al, 2019;Garcia-Ramos et al, 2021;Kellermann et al, 2015Kellermann et al, , 2016Nevado et al, 2021a;Massa et al, 2015;Tosi et al, 2020) and developmental changes in these (e.g., Garcia-Ramos et al, 2015;Wright et al, 2021).…”
Section: A Network System Of Cognitionmentioning
confidence: 99%
“…It may also be assumed that cognitive networks display patterns of segregation and integration (Garcia-Ramos et al, 2015Kellermann et al, 2016;Tosi et al, 2020;Wright et al, 2021). For example, Garcia-Ramos et al (2015) observed that patients with paediatric epilepsy displayed both lower integration and segregation across neuropsychological tests.…”
Section: Segregation and Integrationmentioning
confidence: 99%
See 2 more Smart Citations